2018
DOI: 10.35307/saltel.v1i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Theme Markedness in EFL Students’ Recount Texts: A Systemic Functional Analysis

Abstract: This study is aimed to discover the types and the dominant type of theme markedness in EFL students’ recount texts based on the theory of systemic functional linguistics. Qualitative content analysis approach was utilized in this study. Writing sheets were utilized as the instruments of collecting the data. The data were in the form of clauses taken from 33 recount texts written by second-year students of English literature department of University of Sumatera Utara. Based on the analysis, it was discovered th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 6 publications
2
7
0
Order By: Relevance
“…The result clearly shows that unmarked Theme domineers the Thematic realization in physics text. The other research conducted by [3] also found the same phenomenon even though they observe different genre. [5] also empowers that marked Theme is easily found in spoken discourse rather than written discourse.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…The result clearly shows that unmarked Theme domineers the Thematic realization in physics text. The other research conducted by [3] also found the same phenomenon even though they observe different genre. [5] also empowers that marked Theme is easily found in spoken discourse rather than written discourse.…”
Section: Resultssupporting
confidence: 58%
“…Students need to be given the necessary tools to identify the structure of texts in terms of language, genre, functions, form, linguistic features, words, and intentions in order to lead them to complex analyses of discourses. These in-depth analyses will help students recognize the type of text or articles they are dealing with, that is, whether it is a spoken or written discourse [3], which words, rules, and language characteristics the text contains in order to accomplish a specific purpose.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Text is also called as discourse and it is applied in any medium as well as making sense to those who are knowledgeable (Ganie et al, 2020;Hanafiah et al, 2018). It is also used as a means of communication (Humaizi et al, 2020;.…”
mentioning
confidence: 99%
“…When the Topical Theme places at the first part in a clause; it means that the Theme is simple Theme. But the if the Theme is doing not place at the first element of a clause, it means that the clause combine with the other kind of Theme and it's mean that this kind of Theme is the complex Theme(Hanafiah, Yusuf, and Aswani, 2018).…”
mentioning
confidence: 99%